A Comparison between Return on Assets and Net Profit Margin Together with Total Asset Turnover in Predicting Return on Equity of Thai Listed Companies - Tuvadaratragool, Sumeth (Suan Dusit Graduate School Academic Journal, 2023)
This research was quantitative research using secondary data and aimed to compare between return on assets and net profit margin together with total asset turnover in predicting return on equity of Thai listed companies. Due mainly to financial data availability, 104 and 93 Thai listed companies were used as the sample set of 3 years and 5 years, respectively. The study period was between 2015 and 2019. Statistics used included mean, standard deviation, maximum, minimum, skewness, kurtosis, logarithm, simple regression, and multiple regression. The findings showed that a combination of net profit margin and total asset turnover outperforms return on assets in predicting return on equity, or financial performance, of Thai listed companies at the statistical significance level of 0.05. This study documented the use of return on assets and a combinationof return on assets’ components as Thai listed companies’ return on equity predictors in Thailand.